Disparities in open educational resources - Rudzani Israel Lumadi (Social Sciences and Education Research Review, 2025)
This study focuses on the role that higher education institutions play in addressing these disparities, with the aim of improving academic achievement and reducing educational inequities among under-represented students. The guiding question for this study is